Attitudes Toward Religion Scale development and initial psychometric evaluation among Chinese college students - Wang, Kenneth T.; Cao, Yanmei; Johnson, Austin M.; Parsley, Allison; Xie, Zhongyao; Zhang, Li (2019)
The Attitudes Toward Religion Scale (ATRS) was developed to access the level of interest in and position toward the five state-approved religions in China. Data were analysed across two samples of Chinese college students. With Sample 1 (N = 278), exploratory factor analyses were used to select the 10 ATRS items corresponding to two factors: Interest and Position. With Sample 2, confirmatory factor analyses (N = 270) cross-validated the two-factor oblique model as well as a bifactor model. Cronbach alphas of ATRS subscale scores in the two samples ranged from .75 to .85. ATRS-Interest and Position were both positively associated with number of close relationships with religious people. In addition, negative attitudes toward religion was associated with being religiously proselytised by strangers. Moreover, female students reported more favourable attitudes toward religion compared to their male counterparts. The overall results support ATRS as a psychometrically strong and promising measure.
Keywords: China; Attitude; Religion; Scale Development